Response of Several Varieties and Doses of Mycorrhizal Vesiclea Arbuskula (MVA) and P Uptake to Plant Growth and Yield Sweet Corn (Zea mays saccharata Sturt) - Al Ghifari Ramadhan, Rafly; Sondari, Nunung; Amalia, Lia; Ulfah, Indriana (Ann Publisher, 2024)
The purpose of this study was to study the interaction between sweet corn varieties and mycorrhizal doses on the growth and yield of sweet corn (Zea mays saccharata Sturt) and to obtain the varieties and mycorrhizal doses that can have the best influence on the growth and yield of sweet maize plants (Zea mays saccharata Sturt). The research was conducted in Bumi Wangi Village, Ciparay District, Bandung Regency, West Java Province, with an altitude of 650 meters above sea level. Average rainfall 2417.40 mm/year Inceptisol soil order with soil pH 6.4. The analysis design uses a linear model of Group Random Design (RAK) of the Factorial pattern, with 2 (two) factors. The first factor is the variety (V), and the second is the mycorrhizal dose (M). Quadratic regression analysis is carried out to find the optimal dose of arbuscular vesicle mycorrhizal (MVA) that can produce the highest/maximum sweet corn variety. The results showed that there was an interaction between Sweet Boy, Paragon, and Scada varieties and the dose of mycorrhiza vesicles arbuscular 10 g plant-1 on the growth and yield of sweet corn (Zea mays saccharate Sturt) and the optimum dose of Sweet boy varieties resulted in a cob weight value with the highest kebobit of 6.04 kg plot-1 with an optimal dose of arbuscular vesicle mycorrhiza of 10.09 g plant-1, the Talenta variety produced a cob weight with a lobe of 5.96 kg plot-1 with an optimal dose of arbuscula vesicle mycorrhiza of 9.84 g plant-1, the Paragon variety produced a cob weight with the highest lobe of 6.05 kg plot-1 with an optimal dose of arbuscula vesicle mycorrhiza of 9.68 g plant-1 and the Secada variety produced a cob weight with the highest petals of 5.85 kg plot-1 with an optimal dose of arbuscula vesicle mycorrhiza of 10.07 g plant-1.